تحليل أثر فجوة السيولة على الأداء المالي للمؤسسة الاقتصادية دراسة حالة بنك تجاري خلال فترة زمنية. - أسامة بلة; هيثم طباخ (My University, 2021)
This study aims at the effect of the liquidity gap on the financial performance of the economic institution represented by three Algerian commercial banks, namely, the Development Bank (BDL), the External Bank of Algeria (BEA), the Salam Bank-Algeria (EL SALAM), during the period from (2009-2018), using the analytical method, by analyzing the financial statements submitted by the bank is the field of study, in addition to calculating the evolution of liquidity indicators and financial performance. This study concluded that the liquidity gap has an impact on financial performance and this is reflected in the results obtained. The study also concluded that these banks have achieved good financial performance during the period (2009-2018) by achieving positive results, as these results are reflected in achieving a gap Positive liquidity (excess liquidity) in addition to the positive elements of the various financial statements. ............................................... تهدف هذه الدراسة إلى إبراز تأثير فجوة السيولة على الأداء المالي في المؤسسة الاقتصادية ا ولمتمثلة في ثلاث بنوك تجارية جزائرية هي بنك التنمية المحلية ) BDL (، بنك الجزائر الخارجي ) BEA (،و بنك السلام الجزائر ) - L SALAM ) خلال الفترة الممتدة من )2009-2018(،وذلك باستخدام المنهج التحليلي وهذا بتحليل القوائم المالية المقدمة من - طرف البنك ميدان الدراسة،بالإضافة إلى حساب تطور مؤشرات السيولة والأداء المالي .وقد خلصت هذه الدراسة إلى أن فجوة السيولة لها تأثير على الأداء المالي وهذا ما تعكسه النتائج المتحصل عليها،كما توصلت الدراسة إلى أن هذه البنوك قد حققت أداءا ماليا جيدا خلال فترة ) 2009-2018 ( من خلال تحقيق النتائج الإيجابية ، إذ تنعكس هذه النتائج - في تحقيق فجوة سيولة موجبة )فائض السيولة(،بالإضافة إلى إيجابية مختلف عناصر القوائم المالية.